2005
DOI: 10.34101/actaagrar/16/3290
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Effect of Cropyear on the Yield Potential and Yield Stability of Winter Wheat Varieties

Abstract: Variety selection is one of the most important, determinative elements of sustainable winter wheat production. Yield potential, and yield stability are the most important elements in the variety selection of winter wheat, but baking quality parameters play an important role, too.Several winter wheat varieties were tested for yield and yield stability on chernozem soil in the Hajdúság (in the eastern part of Hungary), in the 2001-2002-2003-2004 cropyears. The management factors were the same for all cropyears. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[44], who found that the lack of water in the reproductive phase caused large crop losses. In addition, several other studies such as Ágoston and Pepó [18] proved that the variety used significantly determined the yield. Árendás et al [45] concluded that the quantitative and qualitative parameters of the crop were primarily determined by the biological-genetic properties of the cultivated varieties and by the nutrient supply capacity of the soil.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[44], who found that the lack of water in the reproductive phase caused large crop losses. In addition, several other studies such as Ágoston and Pepó [18] proved that the variety used significantly determined the yield. Árendás et al [45] concluded that the quantitative and qualitative parameters of the crop were primarily determined by the biological-genetic properties of the cultivated varieties and by the nutrient supply capacity of the soil.…”
Section: Discussionmentioning
confidence: 87%
“…The utilization of the fertilizer can be influenced by a number of factors, including the efficiency of the nutrient that is crucial for increasing crop yield and its quality that reduce the amount of fertilizer inputs and minimize the environmental damages of the cultivated wheat variety [17]. Consequently, the selection of the appropriate wheat variety for specific agroecological parameters is a basic variable for efficient and economical wheat cultivation [18,19]. According to the nutrient uptake dynamics of wheat, the plant takes up 90% of the nutrients needed for crop formation upon its emergence [20].…”
Section: Introductionmentioning
confidence: 99%